A study to assess receipt and utilization of janani suraksha yojana cash incentive among mothers in urban slums of Raipur city, Chhattisgarh, India - Sahu, Divya; Khes Beck, Shanta P.; Soni, G. P.; Ekka, Abha; Dixit, Srishti; Chandrakar, Tripti (International Journal of Research in Medical Sciences, 2019)
Background: Janani Suraksha Yojana (JSY) replaces the National Maternity Benefit Scheme. It was launched by the Government of India in April 2005. The aim was to reduce maternal and neonatal mortality by increasing institutional delivery by providing cash incentive to the beneficiaries as well as the link worker ASHA. Objectives of this study was to assess receipt of Janani Suraksha Yojana (JSY) cash incentive and to assess fields of utilization of Janani Suraksha Yojana (JSY) cash incentive. Methods: A Community based cross-sectional study was conducted among 384 mothers delivered within last one year in urban slum of Raipur city. Study centre was department of community medicine, Pt. J.N.M. medical college Raipur, Chhattisgarh. A pre-designed and pre-tested questionnaire was used to interview the study subjects. Results: Out of total 384 study subject’s cheque of JSY cash incentive was received by 70.83%. All (100%) beneficiaries who received cheque was stipulated amount as per JSY guideline. Reasons for not receiving cheque was no availability of BPL card for those who delivered in accredited private health facility. Other reasons were absconded after delivery, unaware of cash incentive, did not go back to get the cheque when called later, patient shifted to another ward. None of the study subjects who delivered at home received the cash incentive cheque. Realization of cheque was not done by 22.79% of study subjects due to complex procedure to open an account in bank. Cash incentive money was utilized in neonatal care, drugs, food, household activities and some deposited in bank. Conclusions: JSY scheme is definitely functioning well in terms of providing cash incentive cheque of JSY on delivery in Government Health facility. There is need to simplify the procedure to open an account so that beneficiaries can avail cash incentive money. There is need to address the problems to receive cheque in home delivery and accredited Private health facility in addition to motivation for institutional delivery.